Tradisi Mendarahi Rumah di Solok Selatan - Miftahul Jannah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Living Hadith is a new theme that was popularized since the early 2000s. So far, the study of hadith only revolves around the research of the books and their meanings, this situation causes anxiety among the Muhaddisin because it is feared that there will be no renewal produced in the hadith studies. It is on this basis that the hadith experts find a solution so that the hadith research is able to give a new nuance in the realm of study. With the living hadith research model, it is expected to be able to see the symptoms that live in the community, in the form of patterns and structure of behavior that is based on an understanding of the hadith of the Prophet Muhammad. In the order of life the Prophet's figure became a central figure followed by Muslims until the end of time. This is where various problems related to the needs and development of society are increasingly complex and accompanied by a strong desire to apply the teachings of Islam brought by the Prophet Muhammad in different contexts of space and time. Efforts to apply hadith in the socio-cultural context can be said to be a tradition that lives in the midst of society. Like the tradition of bloody houses, this tradition is the application of the hadith of the Prophet about symbolic prayer. Symbolic prayer is permissible in Islam, as long as it is intended only for Allah. This tradition is carried out by slaughtering animals (roosters), the blood of the chicken is circulated around the house to be built with the hope that the house is strong and crowing like a rooster, and the family that occupies it is avoided from bad. This field-based research focuses on the practice of traditional house-bred tradition in Nagari Pulakek, West Sumatra, in this study the writer uses descriptive analytical methods.